Age-dependency of the Propagation Rate of Coronavirus Disease 2019 Inside School Bubble Groups in Catalonia, Spain. Issue 11 (November 2021) - Alonso, Sergio; Alvarez-Lacalle, Enric; Català, Martí; López, Daniel; Jordan, Iolanda; García-García, Juan José; Soriano-Arandes, Antoni; Lazcano, Uxue; Sallés, Pilar; Masats, Marta; Urrutia, Julià; Gatell, Anna; et al.
Abstract : Background: We analyzed contagions of coronavirus disease 2019 inside school bubble groups in Catalonia, Spain, in the presence of strong nonpharmaceutical interventions from September to December 2020. More than 1 million students were organized in bubble groups and monitored and analyzed by the Health and the Educational departments. Methods: We had access to 2 data sources, and both were employed for the analysis, one is the Catalan school surveillance system and the other of the educational department. As soon as a positive index case is detected by the health system, isolation is required for all members of the bubble group, in addition to a mandatory proactive systematic screening of each individual. All infected cases are reported. It permits the calculation of the average reproductive number (R*), corresponding to the average number of infected individuals per index case. Results: We found that propagation inside of the bubble group was small. Among 75% index cases, there was no transmission to other members in the classroom, with an average R* across all ages inside the bubble of R* = 0.4. We found a significant age trend in the secondary attack rates, with the R* going from 0.2 in preschool to 0.6 in high school youth. Conclusions: The secondary attack rate depends on the school level and therefore on the age. Super-spreading events (outbreaks of 5 cases or more) in childhood were rare, only occurring in 2.5% of all infections triggered from a pediatric index case.